A pragmatic guide to business process modelling - Holt, Jon (UK British Informatics Society Limited, 2009)
This updated and expanded edition shows how effective and accurate modeling can deliver a more complete understanding of a business and its requirements. It shows the benefits of using the Unified Modelling Language (UML) and alternative notations.
Includes bibliographical references and index
rua 08/06/16
Loans
Keywords: Process modelling, Enterprise architecture, Automation tools, professional training, UML diagrams, Business process modelling